2001
DOI: 10.1104/pp.125.3.1499
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Inositol 1,4,5-Trisphosphate in Gravitropic Signaling and the Retention of Cold-Perceived Gravistimulation of Oat Shoot Pulvini

Abstract: Plants sense positional changes relative to the gravity vector. To date, the signaling processes by which the perception of a gravistimulus is linked to the initiation of differential growth are poorly defined. We have investigated the role of inositol 1,4,5-trisphosphate (InsP 3 ) in the gravitropic response of oat (Avena sativa) shoot pulvini. Within 15 s of gravistimulation, InsP 3 levels increased 3-fold over vertical controls in upper and lower pulvinus halves and fluctuated in both pulvinus halves over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 41 publications
8
120
0
5
Order By: Relevance
“…A rapid increase and oscillation of inositol 1,4,5-trisphosphate (IP 3 ) levels was found in maize (Zea mays) pulvini after a gravitropic stimulus, lending further support to the role of phospholipid signaling in early gravitropic events (Perera et al, 1999). Perera et al (2001) showed that although cold treatment prevented the gravitropic response, IP 3 concentrations still changed in response to the gravity stimulation. The authors proposed that the cold treatment interrupted the events between IP 3 signaling and the establishment of an auxin asymmetry (Perera et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A rapid increase and oscillation of inositol 1,4,5-trisphosphate (IP 3 ) levels was found in maize (Zea mays) pulvini after a gravitropic stimulus, lending further support to the role of phospholipid signaling in early gravitropic events (Perera et al, 1999). Perera et al (2001) showed that although cold treatment prevented the gravitropic response, IP 3 concentrations still changed in response to the gravity stimulation. The authors proposed that the cold treatment interrupted the events between IP 3 signaling and the establishment of an auxin asymmetry (Perera et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Perera et al (2001) showed that although cold treatment prevented the gravitropic response, IP 3 concentrations still changed in response to the gravity stimulation. The authors proposed that the cold treatment interrupted the events between IP 3 signaling and the establishment of an auxin asymmetry (Perera et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The fastest responses were measured for phospholipase C-mediated changes of IP 3 levels in the cereal pulvini of oat and maize. A transient 5-fold increase in IP 3 within 10 s of gravity stimulation in the lower half of the pulvinus was detected (Perera et al, 1999(Perera et al, , 2001. Within less than a minute of gravity stimulation, changes in the cytosolic pH in the columella cells of the Arabidopsis root cap were evident (Scott and Allen, 1999;Fasano et al, 2001).…”
mentioning
confidence: 97%
“…Our previous pharmacological study using RR (Toyota et al, 2008a) suggests the involvement of endomembrane Ca 2+ -permeable channels in the sustained [Ca 2+ ] c increase. Intracellular inositol 1,4,5-trisphosphate (InsP 3 ) level is known to increase within 15 s of gravistimulation in oat (Avena sativa) shoot pulvini (Perera et al, 2001), suggesting the involvement of phospholipase C (PLC)-dependent signaling in the response to gravistimulation (Perera et al, 2006;Smith et al, 2013). Thus, InsP 3 -induced Ca 2+ release (Gilroy et al, 1990;Franklin-Tong et al, 1996;Knight et al, 1996) provides a potential mechanism for the sustained [Ca 2+ ] c increase that, once triggered, would be less sensitive to the gravity environment.…”
Section: Relationship Between the Amplitude Of The Sustained [Ca 2+ ]mentioning
confidence: 99%